A REVIEW OF THE METHODS USED TO CLASSIFY AND RECOGNIZE PLANT LEAVES (Academicia Globe: Inderscience Research, 2022)
This research aims to comprehensively analyze several techniques utilized in computer vision to automatically identify plants based on photographs of their leaf structures. It's possible that the pictures were shot with a camera attached to a mobile device or with a digital camera set on a tripod. Botanists make use of the information that was collected in order to identify various types of plants and to make use of the therapeutic or other characteristics that plants possess. As we know, plants are extremely important to the Earth's ecosystem since they provide food and shelter and assist in keeping the atmosphere pure and unpolluted. Some of these plants have medicinal properties that can be exploited. One of the most difficult challenges in computer vision is the automated recognition of plant leaves. The Ayurvedic plant leaf identification system will be useful in many areas of society, including medicine, botanical research, and others. Because of developments in image processing and pattern recognition technologies, we can instantly discern leaf pictures. This article overviews the many approaches and categories for identifying papers.